Improving Ionplus MICADAS performance with recessed graphite - Broek, Taylor A. B.; Roberts, Mark L. (Radiocarbon, 2024)
Cathodes with recessed sample surfaces have several benefits in cesium sputter ion sources, including higher output, more efficient use of sample material, and improved focusing of the extracted ion beam. However, the Ionplus MICADAS uses cathodes with a graphite surface that is essentially flush with the sample holder. To evaluate the performance of recessed graphite with the MICADAS and determine the optimal surface depth, we tested four different depths, including the standard (flush) pressing method, 0.5 mm, 1.0 mm, and 1.5 mm. We found that recessed depths of 1.0 and 1.5 mm resulted in 20% higher ion beam current compared to the standard method under the same source conditions. The results are consistent with the beam produced from the recessed targets being more narrowly focused with a lower emittance, resulting in better transmission through the accelerator. Small graphite samples (200 mu g C) with recessed surfaces produced higher currents for longer, leading to a 2-3x increase in sample ionization efficiency. Additionally, there was some evidence that isotopic ratio measurements of recessed samples were more stable over time. Overall, samples recessed to 1 mm depth offered numerous advantages over the standard pressing method and we have subsequently started pressing all MICADAS graphite using this approach.
Place: EDINBURGH BLDG, SHAFTESBURY RD, CB2 8RU CAMBRIDGE, ENGLAND Publisher: CAMBRIDGE UNIV PRESS Type: Article; Early Access
Keywords: AMS; MICADAS; radiocarbon

Optimization of the LLNL/CAMS gas-accepting ion source and 1 MV compact AMS for natural abundance radiocarbon analysis of CO2 - Broek, Taylor A. B.; Moreland, Kimber C.; Ognibene, Ted J.; McFarlane, Karis J.; Brown, Thomas A. (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2022)
The Lawrence Livermore National Laboratory – Center for Accelerator Mass Spectrometry (LLNL/CAMS) 1 MV AMS system was converted from a biomedical AMS instrument to a natural abundance 14C spectrometer. The system is equipped with a gas-accepting hybrid ion source capable of measuring both solid (graphite) and gaseous (CO2) samples. Here we describe a series of experiments intended to establish and optimize 14CO2 measurement capabilities at natural abundance levels. A maximum instantaneous ionization efficiency of 8 % was achieved with 3 % CO2 in helium at a flow rate of approximately 220 µL/min (3.5 µg C/min). For modern materials (e.g., OX I) we measured an average of 240 ± 50 14C counts/µg C, equivalent to a total system efficiency of approximately 3 %. Experimental CO2 samples with F14C values ranging from 0.20 to 1.05 measured as both graphite and directly as CO2 gas produced equivalent values with an average offset of < 2σ.
Keywords: Accelerator mass spectrometry; CO; Gas-accepting ion source; radiocarbon